MD-UNET: Multi-input dilated U-shape neural network for segmentation of bladder cancer. (August 2021) - Ge, Ruiquan; Cai, Huihuang; Yuan, Xin; Qin, Feiwei; Huang, Yan; Wang, Pu; Lyu, Lei
Abstract: Accurate segmentation of the tumour area is crucial for the treatment and prognosis of patients with bladder cancer. However, the complex information from the MRI image poses an important challenge for us to accurately segment the lesion, for example, the high distinction among people, size of bladder variation and noise interference. Based on the above issues, we propose an MD-Unet network structure, which uses multi-scale images as the input of the network, and combines max-pooling with dilated convolution to increase the receptive field of the convolutional network. The results show that the proposed network can obtain higher precision than the existing models for the bladder cancer dataset. The MD-Unet can achieve state-of-art performance compared with other methods.